SEVERE POST-COVID-19 MULTISYSTEM INFLAMMATORY SYNDROME IN 15-YEAR-OLD GIRL - case report - Trajkovska, Vanja; Andonovska, Biljana; Mijovska, Maja Mojsovska; Muminovic, Amela; Popovski, Sasho; Trajkovski, Gjorgji; Karadjozov, Panche (Journal of Morphological Sciences, 2021)
In contrast to adults, SARS â€“CoV-2 mostly leads to a mild illness in children typically manifested with fever, cough and gastrointestinal symptoms. The phenomenon of multisystem inflammatory syndrome in children (MIS-C) emerged during the coronavirus disease 2019 (COVID-19) pandemic.  Children with MIS-C have current or recent exposure to the disease. Reported symptoms include fever or chills, tachycardia, gastrointestinal symptoms, rash, conjunctival injection and mucosal changes with a relative lack of severe respiratory disease. We report a related case of a 15-year-old girl with signs and symptoms of MIS-C and respiratory failure. Multisystem inflammatory syndrome in children (MIDS-C) with respiratory failure is a serious life-threatening condition that requires treatment in an intensive care unit. Invasive mechanical ventilation, invasive monitoring and treatment with combination therapy of antibiotics, corticosteroids, inotropic support, analgosedation, anticoagulation therapy and other lead to successful cure. Keywords : coronavirus disease (COVID 19), children, multisystem inflammatory syndrome  https://doi.org/10.55302/JMS2142072t